Welding rod preparation process and welding method for wear-resistant layer on surface of titanium alloy drill rod
By preparing titanium-based composite powder and making welding rods, the problem of poor wear resistance of titanium alloy drill rods is solved, efficient and economical wear-resistant layer preparation is achieved, and the service life of the drill rods is extended.
Patent Information
- Application Number
- CN202510253055.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-25
AI Technical Summary
Titanium alloy drill rods have poor wear resistance in actual applications, which leads to rapid wear of the drill rod joints, affecting service life and increasing replacement frequency and cost.
Using an welding rod preparation process, weld rods suitable for use on the surface of titanium alloy drill rods are prepared by mixing titanium alloy powder with carbon powder. After pressing, sintering and forging, weld rods suitable for use on the surface of titanium alloy drill rods are prepared, and the wear-resistant layer is clad on the surface of the drill rods by manual tungsten argon arc welding.
The secondary utilization of resources is realized, the cost is reduced, the hardness and wear resistance of the wear-resistant layer are improved, the compatibility and bonding force between the wear-resistant layer and the drill rod matrix is enhanced, and the service life of the drill rod is extended.
Smart Images

Figure CN119870792A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of petroleum drilling equipment, in particular to a welding rod preparation process and a welding method for a wear-resistant layer on the surface of a titanium alloy drill rod. Background Art
[0002] In the field of oil and gas extraction, as exploration and development advances to deeper and more complex formations, the demand for the extraction of oil and gas wells in complex working conditions such as deep wells, extended displacement wells, sulfur-containing wells, short radius wells, and high-temperature and high-pressure wells is growing. Titanium alloy drill pipes have shown good application prospects in such complex working conditions due to their high specific strength, high temperature resistance, corrosion resistance and other excellent properties. Its high strength and low density characteristics can not only effectively reduce the weight of the drill pipe itself, reduce the energy consumption and difficulty of drilling operations, but also withstand the high pressure and harsh temperature environment brought by complex formations. Its excellent corrosion resistance can significantly extend its service life in wells containing corrosive media such as sulfur, and reduce the risk of accidents caused by corrosion.
[0003] However, there is a key problem with titanium alloy drill pipes in practical applications - poor wear resistance. During the drilling process, the drill pipe joints frequently rub and collide with the well wall and casing. This continuous friction will cause rapid wear of the drill pipe joints, greatly affecting the overall service life of the drill pipe. Premature wear of the drill pipe not only increases the frequency and cost of replacing the drill pipe, but may also cause underground accidents, seriously affecting mining efficiency and economic benefits.
[0004] To solve this problem, the main response strategy in the industry is to prepare a wear-resistant layer on the surface of titanium alloy drill pipes. Some patents such as CN111139466B, CN111577158B, CN114951642B, CN117548667B, CN116265608B, etc. use laser cladding technology to clad highly wear-resistant spherical powder on the surface of titanium alloy drill pipes. Although laser cladding can effectively improve the wear resistance of the drill pipe surface, this technology has many limitations. On the one hand, laser cladding equipment is expensive and requires professional equipment, which is not conducive to drilling site repair. On the other hand, the wear-resistant material used for laser cladding is usually spherical powder, which is expensive and not conducive to promotion and application. It also limits the application of this technology in drilling site repair.
[0005] Patent CN115365620B uses nickel-based welding materials to clad the wear-resistant layer on the surface of the titanium alloy drill pipe by manual welding. Although manual welding is relatively simple, the compatibility of nickel-based welding materials with titanium alloys is poor, and cracks are very likely to occur during the cladding process, affecting the quality of the wear-resistant layer and the performance of the drill pipe. In addition, this method requires preheating of the substrate before welding. The entire process is cumbersome and has high technical requirements for construction personnel. It is also difficult to achieve efficient and large-scale production applications. Summary of the invention
[0006] In view of this, the present invention aims to propose a welding rod preparation process and welding method for the wear-resistant layer on the surface of titanium alloy drill rods to solve the problems of poor wear resistance of titanium alloy drill rods in the prior art, high cost, poor adaptability of cladding process and weak bonding strength between the wear-resistant layer and the drill rod when manufacturing the wear-resistant layer on the surface of the titanium alloy drill rod.
[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A welding rod preparation process for a wear-resistant layer on the surface of a titanium alloy drill pipe comprises the following steps:
[0009] S1: mixing titanium alloy powder and carbon powder to prepare titanium-based composite powder;
[0010] S2: pressing the titanium-based composite powder into a green compact, and then sintering the green compact into a blank;
[0011] S3: Forging the blank to obtain a finished blank;
[0012] S4: Cutting the finished billet into welding rods.
[0013] This method can prepare welding rods using titanium alloy scraps and carbon powder as raw materials, realizing the secondary utilization of resources and greatly reducing costs. The addition of carbon powder can form a hard phase during subsequent sintering and use, significantly improving the hardness and wear resistance of the wear-resistant layer. Since the welding rod and the titanium alloy drill pipe have similar compositions, the wear-resistant layer and the drill pipe matrix have good compatibility and bonding strength. During the welding process, metallurgical bonding can be better achieved, interface defects and stress concentration can be reduced, the strength between the wear-resistant layer and the drill pipe matrix can be improved, and the service life of the drill pipe can be extended.
[0014] Furthermore, in S1, before the mixing preparation, the titanium alloy powder is pickled and dried to remove impurities on the surface.
[0015] Impurities on the surface of titanium alloy powder, such as oxides, oil stains, etc., will destroy the uniformity of the composition of titanium alloy powder. After removing the surface impurities, the chemical composition of titanium alloy powder is more consistent, and it can be more evenly distributed when mixed with carbon powder, avoiding the problem of component segregation caused by impurities, so that the final prepared titanium-based composite powder has uniform composition. During the cladding process, clean titanium alloy powder can better react metallurgically with the drill pipe matrix to form a strong bonding interface, and improve the bonding strength between the wear-resistant layer and the drill pipe matrix, which helps to prevent the wear-resistant layer from peeling or cracking during use and extend the service life of the drill pipe.
[0016] Furthermore, a hydrogenation-dehydrogenation process is used to prepare the titanium alloy powder after acid washing and drying into a powder with a particle size of 0 to 30 um, and then the titanium alloy powder is mixed with carbon powder, the particle size of the carbon powder is 0 to 10 um, and the weight proportion of the carbon powder in the titanium-based composite powder is 3% to 5%.
[0017] This setting makes it easier to achieve uniform dispersion between titanium alloy powder and carbon powder, and the contact between powder particles is more complete, which can reduce the phenomenon of component segregation and ensure the uniform distribution of various components in the titanium-based composite powder. During the sintering process, the fine carbon powder particles can diffuse into the titanium alloy matrix more quickly, promoting the formation of hard phases such as titanium carbide.
[0018] Furthermore, in S2, the titanium-based composite powder is pressed into a green body by cold isostatic pressing, the cold isostatic pressing pressure is 100 MPa to 150 MPa, and the holding time is ≥10 min.
[0019] This method can make the pressure on the titanium-based composite powder in various parts of the mold uniform, so that the density of the green body is uniform in all directions, reducing the internal stress and defects caused by density differences, ensuring the overall quality of the green body, and can provide sufficient compaction energy for the titanium-based composite powder, so that the gaps between the powder particles are greatly reduced, thereby effectively improving the density of the green body, promoting the densification of the billet, and improving the strength and performance of the final product.
[0020] Furthermore, the green body is sintered into a blank in a vacuum environment, the sintering temperature is 1050° C. to 1150° C., and the holding time is 3 h to 6 h.
[0021] By sintering in a vacuum environment, gas impurities in the green body, such as hydrogen, oxygen, nitrogen, etc., can be effectively removed, preventing the titanium alloy green body from being oxidized during the sintering process, ensuring that the original properties of the titanium alloy are not damaged, and ensuring the stability of the chemical composition and organizational structure of the green body; by controlling the sintering temperature and holding time, the growth of the grains can be effectively controlled to obtain a fine and uniform grain structure, which can not only improve the strength and toughness of the material, but also improve the processing performance and wear resistance of the material.
[0022] Further, in S3, the forging temperature is Tβ+50°C, and the final forging temperature is ≥Tβ-100°C, wherein Tβ is the phase transition point temperature of the billet.
[0023] The initial forging temperature is set to Tβ+50℃. At this temperature, the atomic activity of the titanium alloy is strong, and lattice slip and twin deformation are more likely to occur, which significantly improves the plasticity of the billet and makes it easier for the billet to deform during the forging process, facilitating forging. The final forging temperature is ≥Tβ-100℃, which can ensure that the billet still has a certain plasticity at the end of forging. If the final forging temperature is too low, the titanium alloy will enter a brittle state and will easily produce defects such as cracks when it continues to deform, affecting the quality and performance of the billet. Maintaining a higher final forging temperature can avoid this situation and ensure the smooth progress of the forging process and the integrity of the billet.
[0024] At the same time, forging within this temperature range can effectively refine the grains of titanium alloy. During the high-temperature forging process, the grains will undergo dynamic recrystallization, and the newly generated grains will be finer and more uniform, which can not only improve the strength and hardness of the material, but also improve the toughness and plasticity of the material, so that the prepared welding rod has better comprehensive performance.
[0025] Furthermore, during the forging process, the single deformation is 5% to 10%, and the total deformation is ≥50%.
[0026] This setting can effectively avoid stress concentration inside the material caused by excessive single deformation. When the single deformation is too large, the stress inside the material will increase rapidly and exceed the material's bearing limit, resulting in defects such as cracks and tears. A smaller single deformation can allow the material to gradually adjust its internal structure during the deformation process, evenly bear external forces, and reduce the occurrence of defects. The forging method of multiple small deformations can also help to further compact the material, reduce internal porosity and looseness, make the particles inside the material more closely arranged, and improve the density of the material.
[0027] A welding method, used for the aforementioned welding rod for the wear-resistant layer on the surface of a titanium alloy drill rod, comprising the steps of:
[0028] A1: Use pickling to remove oil stains on the surface of titanium alloy drill pipe;
[0029] A2: Using manual tungsten inert gas arc welding to weld the welding rod onto the surface of the titanium alloy drill pipe;
[0030] A3: After cladding is completed, ultrasonic or heat treatment is used to relieve stress on the cladding area.
[0031] A clean drill pipe surface helps to enhance the bonding force between the cladding layer and the drill pipe matrix. During the cladding process, the welding rod can better diffuse and fuse with the metal atoms on the drill pipe surface to form a tighter bonding interface, which makes it difficult for the wear-resistant layer to separate from the drill pipe matrix when subjected to external forces, thus extending the service life of the drill pipe. Manual tungsten inert gas arc welding is simple to operate and has low technical requirements for construction personnel, making it suitable for large-scale promotion and application. After the cladding is completed, stress relief treatment of the welded parts by ultrasonic or heat treatment can effectively eliminate the residual stress generated during the welding process, rearrange the atoms inside the metal, release stress, reduce stress concentration, and improve the stability and reliability of the welded parts.
[0032] Furthermore, in A2, the welding current is 100A to 150A, and the height of the single-pass cladding layer is ≤3mm.
[0033] This setting can not only meet the welding requirements, but also will not make the drill pipe matrix absorb too much heat. It can effectively control the size of the heat-affected zone, reduce the impact on the drill pipe matrix structure and performance, and avoid problems such as reduced matrix hardness and coarse grains due to overheating, thereby ensuring the overall performance stability of the drill pipe; a single-pass cladding layer height of ≤3mm helps to ensure the quality of the cladding layer. A thinner cladding layer cools faster during the solidification process, which can form a fine and uniform grain structure, improve the hardness and wear resistance of the cladding layer, and at the same time, a thinner cladding layer can also reduce the generation of internal stress, reduce the probability of cracks, make the cladding layer more dense and uniform, and enhance its bonding strength with the drill pipe matrix.
[0034] Furthermore, in A3, the annealing temperature of the heat treatment is 400°C to 600°C.
[0035] Controlling the annealing temperature at 400℃~600℃ can enable metal atoms to obtain sufficient energy to diffuse and migrate, thereby releasing the residual stress generated during the welding process, reducing the stress concentration, and improving the stability and reliability of the welding part.
[0036] Compared with the prior art, the welding rod preparation process and welding method for the wear-resistant layer on the surface of the titanium alloy drill pipe described in the present invention have the following advantages:
[0037] 1) Using titanium alloy scraps and carbon powder as raw materials to prepare welding rods, the secondary utilization of resources is achieved, and the cost is greatly reduced;
[0038] 2) The wear-resistant layer and the drill pipe matrix have good compatibility and bonding strength. During the welding process, they can better achieve metallurgical bonding, reduce interface defects and stress concentration, improve the strength between the wear-resistant layer and the drill pipe matrix, and extend the service life of the drill pipe. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1The metallographic diagram of the welding rod described in Example 1 of the present invention;
[0040] Figure 2 The metallographic diagram of the wear-resistant layer described in Example 1 of the present invention;
[0041] Figure 3 The metallographic diagram of the welding rod described in Example 2 of the present invention;
[0042] Figure 4 The metallographic diagram of the wear-resistant layer described in Example 2 of the present invention;
[0043] Figure 5 The metallographic diagram of the welding rod described in Example 3 of the present invention;
[0044] Figure 6 This is a metallographic diagram of the wear-resistant layer described in Example 3 of the present invention. DETAILED DESCRIPTION
[0045] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0046] Example 1
[0047] Wear-resistant layer material preparation
[0048] TC4 titanium alloy waste chips generated after machining are selected, and the TC4 titanium alloy waste chips are pickled and dried to remove impurities such as oil on the surface. The TC4 titanium alloy waste chips after pickling and drying are prepared into 1um~10um powder by using a hydrogenation dehydrogenation process, and then the titanium alloy powder is mixed with carbon powder to prepare a titanium-based composite powder, wherein the particle size of the carbon powder is 1um~3um, and the weight proportion of the carbon powder is 3%.
[0049] Preferably, titanium alloy scraps with lower cost produced by machining are preferably used. The titanium alloy scraps have the same grade as the titanium alloy drill pipe, or have a similar composition system to the titanium alloy drill pipe. The widely used TC4 titanium alloy can also be selected.
[0050] The prepared titanium-based composite powder is filled in a circular rubber sleeve and is pressed at a cold isostatic pressure of 110 MPa for 30 minutes to prepare a green body. It is then sintered in a vacuum environment at 1050°C for 6 hours and taken out of the furnace to prepare a billet, which is a cylinder with a diameter of φ200 mm.
[0051] Cold isostatic pressing technology is an existing technology and will not be described in detail here.
[0052] The billet is forged by a 2500T hydraulic press to obtain a finished billet. The forging temperature is Tβ+50℃, and the final forging temperature is ≥Tβ-100℃, where Tβ is the phase transition point temperature of the billet. Tβ is 1000℃, that is, the forging temperature is 1050℃, and the final forging temperature is ≥900℃. During the forging process, the single deformation is controlled at 10%, and the total deformation is 50%. Finally, the billet is forged into a rod with a diameter of φ100mm, and there is no crack on the surface of the rod.
[0053] The rods are cut into 1.5mm×1.5mm×400mm welding rods by wire cutting, and then the surface oil is removed by pickling. Figure 1 shown.
[0054] Wear-resistant layer cladding
[0055] When the wear-resistant layer is clad on the surface of the TC4 drill pipe, the oil stain on the surface of the titanium alloy drill pipe is first removed by pickling, and then the electrode is clad on the surface of the titanium alloy drill pipe by manual tungsten inert gas arc welding. The welding current is controlled at 130A to 140A. The thickness of the single-layer cladding layer is 2mm, preferably 1mm to 2mm. Two layers are clad in total, and the total thickness of the cladding layer is 4mm. After each layer of cladding is completed, a handheld ultrasonic effector is used to eliminate the welding stress. Finally, the wear-resistant layer is polished smooth to obtain a wear-resistant layer with a thickness of 3mm. The metallographic image of the wear-resistant layer is as shown in the figure. Figure 2 shown.
[0056] After flaw detection, the wear-resistant layer has no cracks and the hardness is HRC45.
[0057] In Example 1, TC4 titanium alloy waste is prepared into a powder of 1um to 10um, and matched with 1um to 3um carbon powder. The finer powder particle size enables the titanium alloy powder and the carbon powder to contact more fully and mix more evenly, which is beneficial to the diffusion of carbon powder to form a hard phase during subsequent sintering, thereby improving the hardness and wear resistance of the wear-resistant layer. When preparing titanium-based composite powder, it is also beneficial to uniform mixing, reduce component segregation, and ensure product quality.
[0058] The thickness of a single-layer cladding layer is 2 mm. The thinner cladding layer cools quickly and can form a fine and uniform grain structure, thereby improving the hardness and wear resistance of the cladding layer, reducing internal stress and crack generation, and enhancing the bonding strength with the drill pipe matrix.
[0059] Example 2
[0060] Wear-resistant layer material preparation
[0061] TC4 titanium alloy waste chips generated after machining are selected, and the TC4 titanium alloy waste chips are pickled and dried to remove impurities such as oil on the surface. The TC4 titanium alloy waste chips after pickling and drying are prepared into a powder of 0um to 30um using a hydrogenation and dehydrogenation process. The titanium alloy powder is then mixed with carbon powder to prepare a titanium-based composite powder, wherein the particle size of the carbon powder is 0um to 10um, and the weight proportion of the carbon powder is 4%.
[0062] Preferably, titanium alloy scraps with lower cost produced by machining are preferably used. The titanium alloy scraps have the same grade as the titanium alloy drill pipe, or have a similar composition system to the titanium alloy drill pipe. The widely used TC4 titanium alloy can also be selected.
[0063] The prepared titanium-based composite powder is filled in a circular rubber sleeve and is pressed at a cold isostatic pressure of 120 MPa for 50 minutes to prepare a green body. It is then sintered in a vacuum environment at 1100°C for 5 hours and taken out of the furnace to prepare a billet, which is a cylinder with a diameter of φ200 mm.
[0064] Cold isostatic pressing technology is an existing technology and will not be described in detail here.
[0065] The billet is forged by a 2500T hydraulic press to obtain a finished billet. The forging temperature is Tβ+50℃, and the final forging temperature is ≥Tβ-100℃, where Tβ is the phase transition point temperature of the billet, Tβ is 995℃, that is, the forging temperature is 1045℃, and the final forging temperature is ≥895℃. During the forging process, the single deformation is controlled at 8%, and the total deformation is 60%. Finally, the billet is forged into a rod with a diameter of φ100mm, and there is no crack on the surface of the rod.
[0066] The rods are cut into 2mm×2mm×400mm welding rods by wire cutting, and then the surface oil is removed by pickling. Figure 3 shown.
[0067] Wear-resistant layer cladding
[0068] When the wear-resistant layer is clad on the surface of the TC4 drill pipe, the oil stain on the surface of the titanium alloy drill pipe is first removed by pickling, and then the electrode is clad on the surface of the titanium alloy drill pipe by manual tungsten inert gas arc welding. The welding current is controlled at 140A-150A, the thickness of the single-layer cladding layer is 2mm, preferably 1mm-2mm, and two layers are clad in total. The total thickness of the cladding layer is 4mm. After each layer of cladding is completed, a handheld ultrasonic effect instrument is used to eliminate the welding stress. Finally, the wear-resistant layer is polished smooth to obtain a wear-resistant layer with a thickness of 3mm. The metallographic image of the wear-resistant layer is as shown in Figure 4 shown.
[0069] After flaw detection, the wear-resistant layer has no cracks and the hardness is HRC49.
[0070] In Example 2, TC4 titanium alloy waste is prepared into a powder of 0um to 30um and matched with carbon powder of 0um to 10um. The wider powder particle size can further reduce the cost. The rods are cut into thicker welding rods of 2mm×2mm×400mm and a large current of 140A to 150A is used to further improve the cladding efficiency.
[0071] Example 3
[0072] Wear-resistant layer material preparation
[0073] TA31 titanium alloy waste chips produced after machining are selected, and the TA31 titanium alloy waste chips are pickled and dried to remove impurities such as oil on the surface. The TA31 titanium alloy waste chips after pickling and drying are prepared into 10um-30um powder by a hydrogenation and dehydrogenation process, and then the titanium alloy powder is mixed with carbon powder to prepare a titanium-based composite powder, wherein the particle size of the carbon powder is 1um-10um, and the weight proportion of the carbon powder is 5%.
[0074] The prepared titanium-based composite powder is filled in a circular rubber sleeve and is pressed at a cold isostatic pressure of 150 MPa for 10 minutes to prepare a green body. It is then sintered at 1150°C in a vacuum environment for 3 hours and taken out of the furnace to prepare a billet, which is a cylinder with a diameter of φ100 mm.
[0075] The blank is forged by a 2500T hydraulic press to obtain a finished blank. The forging temperature is Tβ+50℃, and the final forging temperature is ≥Tβ-100℃, where Tβ is the phase transition point temperature of the blank, Tβ is 990℃, that is, the forging temperature is 1040℃, and the final forging temperature is ≥890℃. During the forging process, the single deformation is controlled at 5%, and the total deformation is 70%. Finally, the blank is forged into a rod with a diameter of φ30mm, and there is no crack on the surface of the rod.
[0076] The rods are cut into 1.5mm×1.5mm×300mm welding rods by wire cutting, and then the surface oil is removed by pickling. Figure 5 shown.
[0077] Wear-resistant layer cladding
[0078] When the wear-resistant layer is clad on the surface of the TA31 drill pipe, the oil stains on the surface of the titanium alloy drill pipe are first removed by pickling, and then the electrode is clad on the surface of the titanium alloy drill pipe by manual tungsten inert gas arc welding. The welding current is controlled at 100A-120A, the thickness of the single-layer cladding layer is 3mm, and a total of two layers are clad, and the total thickness of the cladding layer is 6mm. After the cladding is completed, annealing is performed at 400℃-600℃, and the heat preservation is carried out for 30 minutes. Finally, the wear-resistant layer is polished smooth to obtain a wear-resistant layer with a thickness of 4mm. The metallographic image of the wear-resistant layer is as follows: Figure 6shown.
[0079] After flaw detection, the wear-resistant layer has no cracks and the hardness is HRC52.
[0080] In Example 3, TA31 titanium alloy scraps are selected, and the weight proportion of carbon powder is 5%. More carbon powder can form more hard phases during subsequent sintering and use, further improving the hardness and wear resistance of the wear-resistant layer.
[0081] The thickness of a single-layer cladding layer is 3 mm. A thicker cladding layer can improve the wear resistance of the wear-resistant layer.
[0082] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A welding rod preparation process for a wear-resistant layer on the surface of a titanium alloy drill pipe, characterized in that: Includes steps: S1: mixing titanium alloy powder and carbon powder to prepare titanium-based composite powder; S2: pressing the titanium-based composite powder into a green compact, and then sintering the green compact into a blank; S3: Forging the blank to obtain a finished blank; S4: Cutting the finished billet into welding rods.
2. The process for preparing a welding rod for a wear-resistant layer on the surface of a titanium alloy drill pipe according to claim 1, characterized in that: In S1, before the mixing preparation, the titanium alloy powder is pickled and dried to remove impurities on the surface.
3. The process for preparing a welding rod for a wear-resistant layer on the surface of a titanium alloy drill pipe according to claim 2, characterized in that: The titanium alloy powder after acid washing and drying is prepared into a powder with a particle size of 0 to 30 um by a hydrogenation and dehydrogenation process, and then the titanium alloy powder is mixed with carbon powder, the particle size of the carbon powder is 0 to 10 um, and the weight proportion of the carbon powder in the titanium-based composite powder is 3% to 5%.
4. The process for preparing a welding rod for a wear-resistant layer on the surface of a titanium alloy drill pipe according to claim 1, characterized in that: In S2, the titanium-based composite powder is pressed into a green body by cold isostatic pressing, the cold isostatic pressing pressure is 100 MPa to 150 MPa, and the holding time is ≥10 min.
5. The process for preparing a welding rod for a wear-resistant layer on the surface of a titanium alloy drill pipe according to claim 4, characterized in that: The green body is sintered into a blank in a vacuum environment, the sintering temperature is 1050° C. to 1150° C., and the heat preservation time is 3 h to 6 h.
6. The process for preparing a welding rod for a wear-resistant layer on the surface of a titanium alloy drill pipe according to claim 1, characterized in that: In S3, the forging temperature is Tβ+50°C, and the final forging temperature is ≥Tβ-100°C, wherein Tβ is the phase transformation point temperature of the blank.
7. The process for preparing a welding rod for a wear-resistant layer on the surface of a titanium alloy drill pipe according to claim 6, characterized in that: During the forging process, the single deformation is 5% to 10%, and the total deformation is ≥50%.
8. A welding method, used for the welding rod for the wear-resistant layer on the surface of a titanium alloy drill pipe according to any one of claims 1 to 7, characterized in that: Includes steps: A1: Use pickling to remove oil stains on the surface of titanium alloy drill pipe; A2: Using manual tungsten inert gas arc welding to weld the welding rod onto the surface of the titanium alloy drill pipe; A3: After cladding is completed, ultrasonic or heat treatment is used to relieve stress on the cladding area.
9. The welding method according to claim 8, characterized in that: In A2, the welding current is 100A~150A, and the height of the single-pass cladding layer is ≤3mm.
10. The welding method according to claim 8, characterized in that: In A3, the annealing temperature of the heat treatment is 400°C to 600°C.
Citation Information
Patent Citations
A wear-resistant strip for titanium alloy oil drill pipe and its preparation method
CN111139466B
A wear-resistant strip welding structure and method for titanium alloy drill pipe joints
CN111577158B
A wear-resistant powder for titanium alloy drill pipe joints and its laser cladding method
CN114951642B
Titanium alloy drill rod joint high-strength wear-resistant belt and preparation method thereof
CN116265608A
Alloy powder and method for preparing titanium alloy drill rod joint wear-resistant belt using the same
CN117548667B